1997
DOI: 10.1046/j.1365-2761.1997.d01-116.x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity and culture studies comparing the Aphanomyces involved in epizootic ulcerative syndrome (EUS) with other similar fungi

Abstract: Pathogenicity and cultural experiments described here provide futher evidence that a distinct species of Aphanomyces is responsible for much of the characteristic pathology of epizootic ulceration syndrome (EUS). Zoospores from 58 fungal isolates were injected intramuscularly in snakehead fish, Channa striata (Bloch). These fungi comprised: Aphanomyces strains isolated from EUS‐affected fish; saprophytic Aphanomyces, Achlya and Saprolegnia spp. from infected waters; and further saprolegniaceous fungi involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 1 publication
3
80
0
Order By: Relevance
“…Furthermore, these techniques distinguished this group of pathogens from a variety of other Oomycete fungi that have been previously shown to be nonpathogenic to EUS-susceptible fish (Lilley & Roberts 1997). The results are consistent with other studies using random amplified polymorphic DNA (RAPDs) and pyrolysis mass spectrometry (PyMS) which also indicate that the EUS, RSD and MG isolates form a homogenous group and are probably conspecific (J.…”
Section: Histochemical Analysissupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, these techniques distinguished this group of pathogens from a variety of other Oomycete fungi that have been previously shown to be nonpathogenic to EUS-susceptible fish (Lilley & Roberts 1997). The results are consistent with other studies using random amplified polymorphic DNA (RAPDs) and pyrolysis mass spectrometry (PyMS) which also indicate that the EUS, RSD and MG isolates form a homogenous group and are probably conspecific (J.…”
Section: Histochemical Analysissupporting
confidence: 87%
“…A List of the fungi used in the present study is given in Table 1 and further details can be found in Lilley & Roberts (1997).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The causative agent is now known to be an invasive, highly pathogenic Oomycete fungus called A. invadans (14,15). This fungus is also the cause of EUS in the IndoPacific region and has caused extensive losses to commercial fisheries there since the early 1970s (11)(12)(13). However, disease outbreaks are considered a multifactorial problem because a variety of predisposing factors may be involved, the only absolute requirement being the presence of the fungus.…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks have been referred to respectively as epizootic ulcerative syndrome (EUS) in Asia, red spot disease in Australia, and mycotic granulomatosis in Japan (12). This disease has devastated several major commercial fisheries, both wild and farmed, and is now collectively referred to as EUS (13). Aphanomyces invadans, an Oomycete fungus, was recently implicated as the etiologic agent of EUS.…”
mentioning
confidence: 99%